Institucionalização do ensino em administração de empresas na cidade de São Paulo: um estudo de caso sobre a Faculdade de Economia, Administração e Contabilidade da Universidade de São Paulo (FEA-USP) - Vale, Miriam Pires Eustachio de Medeiros (2012)
The objective of this study is to understand the process of institutionalization of the undergraduate course in business administration from the Faculty of Economics, Administration and Accounting from the University of São Paulo (FEA-USP), with the theoretical model of Barley and Tolbert (1997). Exploring historical aspects to try to explain the 'spirit of the times' (Zeitgeist) and illustrate the process of emergence of a new undergraduate at USP, the methodology of case study (YIN, 2001) was chosen to allow a wide range of techniques of research. Thus, the study analyzed the Minutes of Meetings of the Congregation of the time (1946-1965), interviews with fifteen people between actors and observers of the history of this institution during the period, newspapers published by the students of the Faculty and bibliography on the subject. Using the concepts found in Giddens (1979, 1986), Machado-da-Silva, Fonseca and Crubellate (2005), DiMaggio and Powell (1983), Hardy and Maguire (2008), Khurana (2007), among others that work with institutional theory, the process of institutionalization of the course of business administration at FEA-USP is analyzed, relating available literature with the facts found in documents and interviews conducted. Some events called attention: the delay in more than a decade to the founding of the FEA at USP, the connection between the discipline “Management Science” with the Institute of Management, which had its genesis from the Department of Public Service, linked to the state government of Sao Paulo. There were people and necessary situations that helped in the setting of the course at USP only from the 60's. In this sense, the roles played by Prof. Antonio Delfim Netto and Prof. Ruy Aguiar da Silva Leme are explored in greater detail because of the great impact that their decisions had in the process of creation and establishment of a management career. In fact, institutions, with emphasis in this research on FEA-USP, are potential sites for the study of change and social actors through their actions undertaken are capable of generating modification or reproduction of the status quo within these establishments. The institutions are possibilities for those who compose them, at the same time, institutions constrain actions and are necessary in society just as it is presented in modernity.